2016
DOI: 10.3945/ajcn.115.122804
|View full text |Cite
|
Sign up to set email alerts
|

Circulating 25-hydroxyvitamin D and physical performance in older adults: a nationwide study in Taiwan

Abstract: The factors associated with vitamin D inadequacy in Taiwan were higher education, higher BMI, and lower fish and milk intakes. No dose-effect relation existed between vitamin D concentration and physical performance except for single-leg stands. This study was registered at www.clinicaltrials.gov as NCT02677831.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Recreational sunlight exposure was inversely associated with FL risk [ 13 ]. A recent study in Taiwan found that vitamin D deficiency in men and women was partly due to lack of sun exposure [ 41 , 42 ]. Further studies are needed to evaluate the association between sun exposure and the development of FL in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Recreational sunlight exposure was inversely associated with FL risk [ 13 ]. A recent study in Taiwan found that vitamin D deficiency in men and women was partly due to lack of sun exposure [ 41 , 42 ]. Further studies are needed to evaluate the association between sun exposure and the development of FL in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Taiwan, including 5664 community-dwelling participants aged 55 years or above, starting in 2008, examined the link between dietary factors and serum 25(OH)D concentrations [59]. Fish consumption was correlated with 25(OH)D concentrations to the p < 0.001 level, with >68.6 g/d intake vs. <12.9 g/d associated with a 14-nmol/L increase for males, whereas for females, >68.6 g/d vs. 0 of rarely was associated with an 11-nmol/L increase in 25(OH)D. Milk consumption was associated with much smaller increases in 25(OH)D concentrations, whereas egg and meat consumption were nonsignificantly inversely correlated with 25(OH)D concentration.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Those who had higher education, higher BMI and lower fish and milk intake were found to be more likely to have vitamin D insufficiency. 24 The results of gait speed and handgrip strength performed by the HALST participants were adopted to refine cutoffs and prevalence of sarcopenia in Taiwan. 25 We also illustrated a synergistic impact of sarcopenia and obesity on elders’ physical performance.…”
Section: What Has Been Found? Key Findings and Publicationsmentioning
confidence: 99%